Oil Prices and How Much Tax the Government Collects - Tran, Trang (Université d'Ottawa | University of Ottawa, 2019)
This paper aims to examine the impacts of oil price on revenues that provincial government collect from 6 sources: personal income tax, corporate income tax, retail sales tax, federal cash transfers, natural resource revenue and other own - source revenue. All the dependent variables are expressed in real value per capita. Oil price is used as the key explanatory available; other explanatory variables include U.S. real interest rate, U.S housing real price index and annual population growth rate in each province in Canada. The data consist of 10 provinces over the period 1980 - 2017. The variables are expressed in first differences to test the impact of oil price because of the non-stationary of the variables. The result suggests that higher oil prices do not show a statistically significant impact on the government’s revenue sources except for natural resource revenue. Higher oil prices have a positive significance impact in the four oil rich provinces. According to the sign and magnitude of the coefficients, Saskatchewan and Alberta are more sensitive to oil price than B.C. and Newfoundland and Labrador.